2001
DOI: 10.1021/ef010074b
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Jet Fuel Freezing by Differential Scanning Calorimetry

Abstract: Differential scanning calorimetry (DSC) was used to study the freezing of jet fuel and the effect of cold flow improving additives. We find that the cooling (freezing) exotherm is a more useful diagnostic tool for this purpose than the heating (melting) endotherm. Jet fuels (Jet A, JP-8, and Jet A-1) display a strong exotherm upon cooling between −45 and −60 °C. By the study of mixtures composed of classes of jet fuel components (normal paraffins, isoparaffins, and aromatics), we find that the cooling exotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…In comparison, the enthalpy of fusion for C10 isoalkanes, cycloalkanes, and aromatics is below 20 kJ mol −1 . 377 However, crystallization also depends on the composition of the non-crystallizing components of the solution in complex ways. 378 The presence of polar oxygen functional groups on an alkyl chain increases the freezing point and reduces solubility (note the following melting points, dodecane: −9.6 °C, 2-dodecanone: 20 °C, dodecanol: 24 °C, dodecanoic acid: 43.2 °C), while the less polar ester group can have little effect (methyl undecanoate: −10 °C).…”
Section: Fuel Utilitymentioning
confidence: 99%
“…In comparison, the enthalpy of fusion for C10 isoalkanes, cycloalkanes, and aromatics is below 20 kJ mol −1 . 377 However, crystallization also depends on the composition of the non-crystallizing components of the solution in complex ways. 378 The presence of polar oxygen functional groups on an alkyl chain increases the freezing point and reduces solubility (note the following melting points, dodecane: −9.6 °C, 2-dodecanone: 20 °C, dodecanol: 24 °C, dodecanoic acid: 43.2 °C), while the less polar ester group can have little effect (methyl undecanoate: −10 °C).…”
Section: Fuel Utilitymentioning
confidence: 99%
“…It has been previously used to study the phase change characteristics of Fuel System Icing Inhibitors [37], and jet fuels with and without additives [30]. The freezing point of neat DiEGME is -70 °C [37].…”
Section: Experimental Determination Of Ice Formation Inhibitionmentioning
confidence: 99%
“…Figures 6 and 7 show that there appears to be no glass transitions and crystallization behavior for any of the biooil products. Studies have reported [24] that the presence of aromatics exhibits a crystallization behavior but the bio-oil products obtained from pyrolysis of algae biomass (with and without lipids) did not exhibit such behavior.…”
Section: Analysis Of the Bio-oil Using Dscmentioning
confidence: 99%
“…The bio-oil produced via pyrolysis of wood biomass is generally composed of aromatics, saturated carbons, alcohols, amines, and acids. Studies have suggested [24] that the aromatics group of compounds show glass transition behavior.…”
Section: Introductionmentioning
confidence: 99%